International students’ loneliness and social engagement: Narratives from the United States and Japan - Ivanova, Polina; Sun, Yi; Li, Wendan; Bista, Krishna (Journal of International Students, 2025)
Despite the increasing global mobility in higher education, international students in the United States and Japan face persistent challenges in the areas of wellbeing and inclusion. This study investigates international students' experiences of loneliness and their social engagement in comparative perspective, focusing on friendships and involvement with volunteer organizations as the most prominent types of social involvement among the participants. Utilizing qualitative data from 15 in-depth interviews conducted during the coronavirus disease (COVID-19) pandemic, this research identifies the limited friendships with domestic students and the underutilized potential of volunteer organizations as key issues. The findings highlight the need for better coordination with external stakeholders to enhance support systems. The study concludes that universities alone cannot address these challenges and recommends fostering collaborations with community organizations to improve international students' social integration and wellbeing.